VIROLOGIC AND IMMUNOLOGIC OUTCOME OF TREATMENT OF HIV INFECTION WITH A HERBAL CONCOCTION, Α-ZAM, AMONG CLIENTS SEEKING HERBAL REMEDY IN NIGERIA - Onifade, A. A.; Jewell, A. P.; Okesina, A. B. (African Journal of Traditional, Complementary and Alternative Medicines, 2010)
This study was to determine the effectiveness (CD4 count and viral load) of a safe herbal concoction, α-Zam used by clients seeking herbal remedy for treatment of HIV infection in Nigeria. 51 patients taking α-Zam as complementary and alternative therapy through the herbal therapist were studied for a period of 16 months. Preliminary medical and laboratory examinations using WHO and CDC criteria were done after confirmation of HIV infection by Western blotting in the nearest teaching hospitals to the residence of the patients. Regular visits were paid to the patients after commencement of the α-Zam to assess the side-effects, drug interactions, toxicity and effectiveness of the herbal remedy. There was a statistical significance (P<0.05) between pre-treatment and post-treatment CD4 count. 4 (7.8%) of the patients had average increase in CD4 count of 262±16 cell/µL, 23 (45.1%) patients with average increase 310±16 cell/µL, 16 (31.4%) patients with average increase 456±25 cell/µL and 8 (15.7%) patients with average increase 510±36 cell/µL( %) were at WHO staging I , II, III and IV respectively within 4 months on herbal therapy. There was very marked reduction in viral (HIV-RNA) load with 41 (80.4%) and10 (19.6%) HIV infected patients had undetectable viral load and <1000 copies/ml respectively after the therapy. All symptoms and signs associated with HIV infection in all patients fully subsided within 4 weeks of commencement of α-zam therapy and there was no evidence of negative drug interaction in those HIV patients using both the herbal and highly active anti-retroviral therapy (HAART). The study is in progress to determine periodic immunological outcomes of post therapy in all patients.